Nick and Tesla's special effects spectacular : a mystery with animatronics, alien makeup, camera gear, and other movie magic you can make yourself - Pflugfelder, Bob, 1967-; Hockensmith, Steve (Quirk Books, 2015)
"Hollywood has come to Half Moon Bay as kid inventors Nick and Tesla find themselves on the set of a big-budget superhero movie. But someone's sabotaging the on-screen debut of their favorite comic book hero, so the brother and sister sleuths must sneak behind the scenes to save the show. Luckily, they have help from an arsenal of homemade special-effects gadgets. This cinematic saga includes instructions for creating camera gear, stunt dummies, make-up magic, and more!"--Back cover.